2016
DOI: 10.1016/j.jallcom.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and strain hardening behavior of phase reversion-induced nano/ultrafine Fe-17Cr-6Ni austenitic structure steel

Abstract: Nano/ultrafine-grained (Nano/UFG) structure was obtained in Fe-17Cr-6Ni austenitic steel using a combination of severe cold deformation and reverse-transformation annealing. The microstructural evolution during severe cold reduction and annealing was studied to elucidate the effect of grain size on mechanical properties and strain hardening behavior. Austenitic steel with the smallest average grain size of ~220 nm was obtained and exhibited a good combination of high strength and high ductility when the cold r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However The dislocation structure in the as-extruded Mg-4Zn sample was similar to dislocation cells, which are formed by a high-density dislocation area when the dislocation density reaches a certain value. Due to the activation of multiple slip, the dislocation density rapidly increased and the high-density dislocation areas transformed into dislocation cells [28,29] . Therefore, dislocation cell formation requires a sufficiently high dislocation density.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However The dislocation structure in the as-extruded Mg-4Zn sample was similar to dislocation cells, which are formed by a high-density dislocation area when the dislocation density reaches a certain value. Due to the activation of multiple slip, the dislocation density rapidly increased and the high-density dislocation areas transformed into dislocation cells [28,29] . Therefore, dislocation cell formation requires a sufficiently high dislocation density.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of dislocation cells means that there is a relatively high dislocation density in this alloy [28] . Furthermore, in stage IV strain hardening, active dislocations could be continuously absorbed by the boundaries of dislocation cells [29] . Dislocation cells would convert to sub-boundaries (low-angle grain boundaries) when they absorbed enough mobile dislocations.…”
Section: Rate Of Dislocation Storage In the As-extruded Mg-zn Alloysmentioning
confidence: 99%
“…In fact, many commercial ASSs are metastable against the martensitic transformation during deformation. As a result, cold deformation below a specific temperature is accompanied by the transformation of austenite to martensite and the resulting inhibition of necking, which is known as transformation‐induced plasticity (TRIP) effect . Järvenpää et al reported a two‐stage hardening behavior for AISI 301LN austenitic steel while investigating the effect of grain size: first, the work‐hardening rate decreases rapidly, reaching a minimum at a certain strain, and then, when the martensite formation reaches a rate high enough, the work‐hardening rate starts to increase reaching a maximum.…”
Section: Introductionmentioning
confidence: 99%
“…Metastable austenitic stainless CreNi-steels are widely used in the chemical and petrochemical industries, in power plants, as well as in the food industry, automotive industry and medical technology and are therefore of great economic importance [3,4]. This group of steels can be hardened by strain hardening mechanisms like twin formation, grain refinement and an increase in the dislocation density [5,6] as well as by martensitic phase transformation from g-austenite to εand a 0 -martensite (see Fig. 1) [7,8].…”
Section: Introductionmentioning
confidence: 99%